Co-Designing Culture: Ethical Frameworks for Digital Representation of Batik Motifs - Rusnalasari, Zulidyana Dwi; Hermansyah, Kusen Dony (Indonesian Scientific Publication, 2025)
The digital reinterpretation of Batik, a UNESCO-recognized Intangible Cultural Heritage, presents both opportunities and ethical challenges. This study explores the boundaries of cultural remixing through a mixed-methods approach combining user experience (UX) testing, qualitative interviews, and legal-normative analysis. Forty illustrators participated in a task-based UX experiment to assess perceptions of usability, aesthetic value, and ethical alignment when reimagining Batik motifs. Senior illustrators exhibited higher ethical sensitivity and design fidelity, as confirmed by ANOVA. Stakeholder interviews with artisans, curators, and designers revealed themes emphasizing respect for pakem (traditional rules), the importance of community participation, and risks of symbolic dilution. Legal analysis of Indonesian Copyright Law and UNESCO ICH guidelines highlighted gaps in enforcement and the need for soft-law instruments such as ethical toolkits and participatory protocols. Findings suggest that responsible innovation requires integrated frameworks combining legal, educational, technological, and participatory strategies. A Digital Ethics Toolkit is proposed to support designers in navigating cultural representation responsibly. This toolkit includes a pakem rubric, attribution checklist, AI output review system, and co-design templates. The study concludes that safeguarding heritage in digital contexts must involve collaborative stewardship, where ethical awareness and cultural dialogue shape innovation.